Efficiency of Method of Phonosematic Analysis in Translation of Sound Descriptive Vocabulary into Russian (on Material of Japanese Poetic Texts Haiku) - E. I. Krivosheyeva (Научный диалог, 2017)
The article is devoted to consideration of efficiency of the method of phonosematic analysis in the translation of sound descriptive vocabulary from Japanese into Russian in the most capacious genre of Japanese poetry - haiku. The relevance of the topic is dictated by the lack of clearly defined principles of translation of sound descriptive lexis in general and by the translators ignoring the ability of phonetic units and the sound organization of the text to act as a carrier of emotional content in particular. The article shows that the traditional principles of translating non-equivalent vocabulary, which includes sound descriptive words, are not effective in the case of the Japanese language, mostly because of the peculiarities of Oriental lyric poetry, rooted in the philosophy of Buddhism, Zen (chin. Chan ) and the national world view, which, in turn, is based on imagery and innuendo. On the material of poetic works by the famous Japanese poet Issa Kobayashi (1763-1828), full of onomatopoetical vocabulary, the features of the semantic structure of sound descriptive words are identified, phonetic means are determined, not only relevant for the adequate representation of this structure, but also for ensuring the unity of form and meaning of sound descriptive words.